A study of cloud-to-ground lightning flashes initiated by fast positive breakdown - Ahmad, Mohd Riduan; Mohammad Sabri, Muhammad Haziq; Al-Kahtani, Ammar Ahmed; Shamsul Baharin, Shamsul Ammar; Ab Kadir, Mohd Zainal Abidin; Nordin, Farah Hani; Lu, Gaopeng; Zhang, Hongbo; Williams, Earle; Cooray, Vernon (Elsevier Ltd, 2022)
In this paper, we examine the initiation event of two tropical negative cloud to ground (CG) lightning flashes within reversal distance (<8 km) detected on 12 (CG1) and 24 (CG2) November 2019, respectively. The CG flashes were recorded using a fast antenna (FA), slow antenna (SA), magnetic field (B-field), and very high frequency (VHF) sensors located at two observation stations (ST1 and ST2) 13.26 km apart. The key finding is that CG1 flash was initiated by a short VHF pulse followed by a VHF burst (fast positive breakdown) while CG2 flash was initiated by a VHF burst (fast positive breakdown) not preceded by a short VHF pulse. The VHF burst was a precursor for initiation of a narrow bipolar event (NBE)-like pulse and initial electric field changes (IECs). Based on the VHF interferometer map, the VHF sources of NBE-like pulses have been propagated upward predominantly vertical. The initiation altitude, total length of the VHF sources propagation, estimated velocity of NBE-like pulse for CG1 flash were 4.5 ± 0.5 km, 1.9–3.8 km, and 2.4 × 108 to 4.8 × 108 ms−1, respectively, and for CG2 flash were 5.1 ± 0.8 km, 0.2–3.0 km, and 2.7 × 107 to 4.1 × 108 ms−1, respectively. It is evident that IECs process has been initiated during fast positive streamers propagation. It can be suggested that the IECs process resulted from charge transfer during a fast positive breakdown. The durations and magnitudes of IECs for CG1 flash were 248.5 μs and 27.97 V/m, respectively, and for CG2 flash were 265.8 μs and 2.31 V/m, respectively.